2015
DOI: 10.1021/acsami.5b01954
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting the VIM-2 Metallo-β-Lactamase by Graphene Oxide and Carbon Nanotubes

Abstract: Metallo-β-lactamases (MBLs) degrade a broad spectrum of antibiotics including the latest carbapenems. So far, limited success has been achieved in developing its inhibitors using small organic molecules. VIM-2 is one of the most studied and important MBLs. In this work, we screened 10 nanomaterials, covering a diverse range of surface properties including charge, hydrophobicity, and specific chemical bonding. Among these, graphene oxide and carbon nanotubes are the most potent inhibitors, while most other mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…Moreover, protein adsorption by nanomaterials, not least by GO, which presents a vast surface for protein binding, can lead to inhibition of enzyme activity. Hence, recent studies have shown that carbon-based nanomaterials can inhibit the bacterial enzyme, VIM-2 belonging to the clinically relevant class of metallo-β-lactamases that provide resistance to a broad spectrum of antibiotics including penicillin; the inhibition was noncompetitive and was attributed to hydrophobic interactions with the enzyme [90]. Moreover, adsorption of VIM-2 was further probed using protein displacement assays and it could not displace or be displaced by BSA.…”
Section: Bio-corona Formation On Carbon-based Nanomaterialsmentioning
confidence: 99%
“…Moreover, protein adsorption by nanomaterials, not least by GO, which presents a vast surface for protein binding, can lead to inhibition of enzyme activity. Hence, recent studies have shown that carbon-based nanomaterials can inhibit the bacterial enzyme, VIM-2 belonging to the clinically relevant class of metallo-β-lactamases that provide resistance to a broad spectrum of antibiotics including penicillin; the inhibition was noncompetitive and was attributed to hydrophobic interactions with the enzyme [90]. Moreover, adsorption of VIM-2 was further probed using protein displacement assays and it could not displace or be displaced by BSA.…”
Section: Bio-corona Formation On Carbon-based Nanomaterialsmentioning
confidence: 99%
“… 38 Verona integron-encoded-2 (VIM-2), a subclass of MBLs, is a negatively charged protein with Zn 2+ -dependent enzyme activity. 39 In a systematic investigation by Huang and co-workers, 40 the effects of various nanomaterials on VIM-2 catalytic activity were explored. Among the ten nanomaterials examined with different surface properties, graphene oxide (GO) and carbon nanotube (CNT) exerted significant inhibitory effects on VIM-2 in a dose-dependent manner ( Figure 7A and B ).…”
Section: Nanozyme As β-Lactamase Inhibitorsmentioning
confidence: 99%
“…Three azolylthioacetamide derivatives reported by Xiang et al were characterized as inhibitors with mixed inhibition mechanism (competitive and uncompetitive), however, their uncompetitive inhibition mechanism and binding site has not been reported [81]. At the time of writing, allosteric inhibition has proven a viable strategy only by using macromolecules, such as DNA nanoribbons, DNA aptamers, camelid nanobodies, graphene oxides and nanotubes [82][83][84][85].…”
Section: Allosteric Effectors and Mechanisms In Class B Blsmentioning
confidence: 99%